Evaluating The Vertebral Structure Using Ultrasound Examination At Manually Identified Midpoint Of Intracristal Line In Pregnant Women - Faheem Ansari, Mohd; Agarwal, Akshat; Swetha Soni, Edamakanti; Shahid, Razi; Rao, M Srinivas (Journal of Neonatal Surgery, 2025)
Introduction: In order to deliver subarachnoid blocks, the intercristal line and associated vertebral level have historically been found by manual palpation. However, an alternate method for precise vertebral identification is ultrasound examination. Aim and Objective: To study the vertebral structure using ultrasound examination at manually identified midpoint of intracristal line in pregnant women. Material and Methods: This was a cross-sectional study conducted in the Department of Surgery with collaboration with Department of Anesthesia. It involved 200 pregnant women at term. Two independent observers estimated the vertebral space at the intercristal line– one using manual palpation and the other using ultrasound guidance. Determining the vertebral structure utilising ultrasound examination at the manually designated midway of the intercristal line in term pregnant women was the main outcome evaluated. Assessing the accuracy of manual palpation in identifying vertebral levels in comparison to ultrasound examination and analysing variables like Body Mass Index (BMI) that may affect the accuracy of vertebral level identification were the secondary outcomes evaluated. Results: The study included 200 pregnant women with a mean age was 22.81±3.75 years in the study population. The mean gestational age (weeks) was 38.95±1.15 in the study population. The minimum gestational age was 37 weeks, and the maximum was 41 weeks. The mean pre-pregnant weight (kg) was 52.85±9.50 in the study population. The ultrasonographic assessment revealed that the manually palpated intercristal line corresponded to the L4 vertebra level in 50% of cases, the L3-L4 intervertebral space level in 30%, the intended L4-L5 intervertebral space level in 15%, the L5 vertebra level in 3%, and the L3 vertebra level in 2%.ultrasound examination showed that the manually palpated intercristal line was higher than the L4 vertebra or L4-L5 intervertebral space in 32% of the pregnant women. Conclusion: According to the study, ultrasound examination, as opposed to manual palpation, may provide a more accurate way to identify spinal structures in pregnant women at term